2011
DOI: 10.1007/s13304-011-0043-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open distal gastrectomy for locally advanced gastric cancer: a case–control study

Abstract: In a non-specialized setting, laparoscopic distal gastrectomy (LDG) for locally advanced diseases remains controversial, particularly given to the technical demands of the learning curve required to perform an adequate resection with D2 lymph node dissection. Inclusion criteria for this statistically generated matching controlled study were all patients who underwent subtotal laparoscopic gastrectomies from January 2006 until September 2009 for locally advanced gastric adenocarcinoma (stage II-IIIb), compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
100
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(104 citation statements)
references
References 38 publications
4
100
0
Order By: Relevance
“…Francescutti and colleagues 27 have reported the only previous Canadian experience, but they included patients with benign lesions as well as those with malignant ones. All comparative studies have reported decreased or similar early postoperative morbidity with LAG ranging from 0% to 26%, [15][16][17][26][27][28][29]31 which compares with our results. Other benefits of the laparoscopic ap proach, including decreased time to ambulation and resumed diet, decreased consumption of analgesia and a shorter length of stay, have been reported in these studies.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Francescutti and colleagues 27 have reported the only previous Canadian experience, but they included patients with benign lesions as well as those with malignant ones. All comparative studies have reported decreased or similar early postoperative morbidity with LAG ranging from 0% to 26%, [15][16][17][26][27][28][29]31 which compares with our results. Other benefits of the laparoscopic ap proach, including decreased time to ambulation and resumed diet, decreased consumption of analgesia and a shorter length of stay, have been reported in these studies.…”
Section: Discussionsupporting
confidence: 88%
“…Others reported no difference between the laparoscopic and open approaches. 15,16,[26][27][28][29][30][31]33 In a meta-analysis of RCTs comparing laparoscopic and open approaches for early gastric cancer, Ohtani and colleagues 9 concluded that there was a lesser number of LNs with laparoscopy. Debate is still ongoing about the extent of the lymphadenectomy and the number of LNs needed in the specimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the ongoing controversy about whether laparoscopic gastrectomy with D2 lymph node dissection for gastric cancer is safe and effective, the most recent studies showed that laparoscopic D2 lymph node dissection was a safe procedure for AGC if the surgery was performed by experienced surgeons [18][19][20][21][22]. Recently, there were several published reports of a case-control study that compared LAG to OG for AGC [20][21][22]. However, these reports did not have sufficient numbers of patients or a follow-up period long enough to compare the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the reported studies of totally laparoscopic subtotal gastrectomy (16)(17)(18)(19), these data suggest that our method of intracorporeal anastomosis using only stapling devices is safe and feasible, and offers a better or equally good early surgical outcome. Totally laparoscopic distal gastrectomy has been spotlighted since all of the procedures may be performed intracorporeally.…”
Section: Discussionmentioning
confidence: 64%